Desain Optimal Tata Letak Fasilitas Dengan Menggunakan Metode CORELAP dan Algoritma CRAFT - Kadek Yaniza Ayu Tantri Devi; Prabowo, Rony (Universitas Negeri Gorontalo, 2023)
UD. Doa Emak is an appropriate technology business engaged in the manufacture of tools or machines of various models and sizes. UD Doa Emak accepts production requests that vary according to customer requests. There is increasing customer demand and product variations, UD owners. Doa Emak expands the production area so that currently there is empty land that has not been utilized. The land area owned by UD. Doa Emak is 623 m2 with a percentage of vacant land of 48%. By utilizing vacant land, it is possible to increase utilities and optimize machine arrangement so that the transfer distance becomes more efficient and production capacity will increase. This research will solve the problem of production facility layout by redesigning the layout using the CORELAP (Computerized Relationship Layout Program) method, the CRAFT Algorithm (Computerized Relative Allocation of Facilities Techniques) and will be simulated with Flexsim Simulation to provide alternative decisions on the proposed layout. From this study, the results of the CRAFT method were more optimal than the initial layout with a large OMH depreciation of Rp. 49662,6 and efficiency percentage of 3,29%. Simulations using flexsim software produced a total traveled of 115843 m/month.